Exploring cost trajectories of patients admitted to short-term residential care in the Netherlands - Eline D. Kroeze; Janet L. MacNeil Vroomen; Astrid Preitschopf; Anneke J. A. H. van Vught; Bianca M. Buurman (PLoS ONE, 2026)
Objective Short-term residential care (STRC) is a Dutch form of post-acute care intended to return older adults home to live independently, yet fewer than 55% of patients are discharged home. Because post-acute care costs are unevenly distributed, average cost trajectories may obscure clinically meaningful variation. This study examines variation in STRC cost trajectories and identifies patient characteristics associated with high-cost group membership. Methods We conducted a retrospective longitudinal observational study using national health claims data from Statistics Netherlands for patients admitted to STRC between 1 February and 31 July 2022. Reimbursed costs across seven categories (STRC, inpatient and outpatient hospital care, district care, long-term care at home, nursing home admission, and geriatric rehabilitation) were measured from one month before to five months after admission. We defined a palliative care group a priori and applied group-based trajectory modelling to the remaining cohort. Two logistic regressions assessed patient-level predictors of high-cost membership. Results Among 16,278 patients, mean six-month costs were €29,859 (SD = €21,088). We identified an a priori palliative care group (n = 3,277; €23,200), a latent high-cost (n = 3,205; €58,478) and a latent low-cost (n = 9,796; €22,723) group. The high-cost group accounted for 39% of total costs, with the largest shares attributable to hospital care, nursing home admission, and longer STRC stays. These patients were more often readmitted to hospital within two weeks of discharge (16.9% versus 3.2%) and discharged to a nursing home (29.8% versus 10.7%). Dementia, institutional living, and several diagnosis groups (including stroke, oncology, organ failure, and cardiovascular disease) were associated with high-cost membership, but overall explanatory power was low (McFadden pseudo R² ≤ 0.05). Conclusions STRC cost trajectories were highly skewed and poorly predicted by routinely available patient characteristics, suggesting cost variation reflects differences in care delivery more than patient case-mix. These findings point to three priorities: strengthening transitions from STRC back to home, critically evaluating STRC placement for patients likely to require nursing home admission, and scrutinizing hospital use during STRC episodes. Cost trajectories offer a promising outcome measure for evaluating intermediate and integrated care.